The Influence of Spiritual Leadership, Work Life Quality, Islamic Work Ethic on Employee Performance with Organizational Citizenship Behavior. - Nasution, Nasir; Marpaung, Muslim; Amirulsyah, Amirulsyah (Opción, 2019)
This study aimed to determine the effect of spiritual leadership, work life quality , and Islamic work ethic on organizational citizenship behavior, and to determine the effect of organizational citizenship behavior on the perfor- mance of employees of SUMUT Islamic Bank in Medan. This research used quantitative approach by conducting a survey of 131 respondents of SUMUT Islamic Bank employees in Medan City with a random sampling method. The analytical tool used in this study was Path Analysis. The results of this study indicated that the quality of work life and Islamic work ethic were proven to have a positive and significant effect on organizational citizenship behavior of employees of the SUMUT Islamic Bank in Medan City. Likewise, organ- izational citizenship behavior had a positive and significant impact on the performance of employees of the SUMUT Islamic Bank in Medan. The results also showed that there was no significant influence between spiritual leader- ship on organizational citizenship behavior. Based on the results of this study, it is recommended that banking stakeholders, especially the managerial of the North Sumatra Bank of Islamic in Medan, be more intensive and massive in paying attention to the determinants of performance, namely by paying atten- tion to the quality of work life and the Islamic work ethic of employees. The originality of this study is that a similar model with a multivariate approach has not been found in the employees of SUMUT Islamic Bank in Medan.